EVALUATION INDIVIDUAL LEVEL OUTCOME OF NUTRITION EDUCATION IN SURABAYA PREGNANT WOMEN CLASS PROGRAM - Maryam Jamilah; Lailatul Muniroh; Dominikus Raditya Atmaka (The Indonesian Journal of Public Health, 2023)
Introduction: Pregnant women class is one of the nutrition education programs and its success can be assessed by its outcomes. Aims: to evaluate the outcome of nutrition education in pregnant women class at individual level in Surabaya on 2019. Method: This research was a descriptive qualitative study using purposive sampling technique to each informant in 4 public health services (Puskesmas) in Surabaya that is Kedungdoro, Wonokusumo, Siwalankerto and Asemworo. Informants in this study were 2 staff from Family Health and Community Nutrition Section at Health Department of Surabaya, 4 nutrition workers, 7 midwives, 4 pregnant women cadres and 9 pregnant women class participants in 2019. Result: show that outcome of nutrition education in pregnant women class program at individual level is mothers’ behavior in consuming high iron foods increase during pregnancy, frequency and portions of mother's meals increase during pregnancy and breastfeeding, mother’s practice of EIB and exclusive breastfeeding. Conclusion: Effect of the nutrition education in pregnant women class on compliance with consuming iron supplementation tablets and PMT biscuit for pregnant women is not yet known and needs to be studied further.